THE INFLUENCE OF COMPENSATION, MOTIVATION, AND JOB SATISFACTION ON EMPLOYEE TURNOVER AT XYZ HOTEL CIMAHI - Restu Andika, Alvin Dwi; Ghazali, Achmad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to analyze the influence of compensation, motivation and job satisfaction on the level of employee turnover at XYZ Hotel located in Cimahi. The problem of high employee turnover can have a negative impact on the smooth running of hotel operations, as well as increasing employee recruitment and training costs. Therefore, this research tries to identify the factors that contribute to employees' decisions to stay or leave the company. The research method used is a quantitative approach with data collection techniques through questionnaires to employees at XYZ Hotel. The data analysis technique used is multiple linear regression to determine the relationship between compensation, motivation and job satisfaction variables and employee turnover levels. The research results show that these three variables have a significant influence on employee turnover, with compensation as the most dominant factor in determining an employee's decision to stay. Motivation and job satisfaction have also been shown to play an important role, although their influence is slightly smaller than compensation. Therefore, it is recommended that XYZ Hotel management improve compensation policies and increase employee motivation and job satisfaction to reduce employee turnover rates and increase more stable employee retention.